Existential Anxiety of Nurses in the COVID‐19‐Virus Units and Its Relation With Resilience and Posttraumatic Growth - Asma Ghonchehpour; Farshid Rafiee Sarbijan Nasab; Fatemeh Maghsoudi; Roghayeh Mehdipour‐Rabori (Health Science Reports)
ABSTRACT Aim The study aimed to investigate the relationship between existential anxiety, posttraumatic growth, and resilience in nurses working in COVID‐19units. Design The study was a descriptive‐analytical study. Methods The researchers conducted the study on 224 nurses working in the COVID‐19units of four hospitals affiliated with Kerman University of Medical Sciences in Southeast Iran from 2021 to 2020 with census method. the data were collected using a demographic questionnaire, Masoudi Sani et al.'s existential anxiety questionnaire, the Conner‐Davidson resilience scale, posttraumatic growth inventory. Results The mean age of nurses were 30.88% ± 6.53% and 76.3% of them were female. The results showed there were a negative and significant correlation between posttraumatic growth and resilience (p < 0.001, r = −0.38) but no statistically significant relationship between existential anxiety, resilience, and posttraumatic growth (p > 0.05). Regression analysis indicated a negative and significant relationship between posttraumatic growth and resilience, but no statistically significant relationship between existential anxiety, resilience (p = 0.28), and Posttraumatic growth (p = 0.20). There was no significant difference between the mean existential anxiety score, age, sex, and education level, but the mean existential anxiety score in the emergency personnel was significantly higher than of other departments. Conclusion The results demonstrated that the mean scores of existential anxiety, resilience and posttraumatic growth were moderate. The researchers suggest educational and interventional measures to improve resilience, posttraumatic growth and reduce existential anxiety among nurses.